KONSEP EVALUASI PENDIDIKAN DALAM PERSPEKTIF ALQURAN - Syahril, Syahril (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with the concept of education evaluation from the Qurâanic perspective. Evaluation is a popular term much used in education to know a studentâs performance in education. In this context, in the Qurâan, we also findÂ  some terms that have similarÂ  meaning with evaluation. For example, al-inbaâ, al-hisab, al-bala, al-nadzar, al-wazn, al-fitnah al-taqdir . These terms are used by the Qurâan to evaluate Godâs servants, eitherÂ  those who believe or disbelieve in God. To know further, how and in which context the Qurâan uses those terms, the usages of the terms are elaborated in this article.Kata Kunci: evaluasi pendidikan, Alquran, al-fitnah, al-hisab, al-wazn, al-taqdir